Urgensi Independensi Dan Restrukturisasi Kekuasaan Kehakiman Di Indonesia - Sri Hastuti Puspitasari (Fakultas Hukum Universitas Islam Indonesia, 2007)
Judicature as a point spear of law enforcement and justice must be independent. The indendency has to be guaranteed by Constitution. However, the rules which stipulate on the constitution has to be formulated clearly in order to achieve certainty. Besides that, independency has to be supported by institutions. The raise of Judicial Commission will triggers the independency of judicature institutions. Furthermore, when in society it raised judicature institutions outside the conventional judicature, it needs a restruction of the institutions in order to structure of the institution which has the highes institution on the Supreme Court.